Rebuilding after war: micro-level determinants of poverty reduction in Mozambique - Simler, Kenneth R.; Mukherjee, Sanjukta; Dava, Gabriel; Datt, Gaurav (International Food Policy Research Institute, 2003)
Rather than looking at the association between poverty and various household and individual characteristics on a one-to-one basis (bivariate analysis), which often oversimplifies complex relationships and can lead to erroneous conclusions, this report uses multiple regression to analyze poverty and living standards econometrically. As methodological choices can have a strong influence on the results,much of the report is given over to a detailed discussion of the methodology used to conduct the analysis and sensitivity analysis to assess the robustness of the findings to alternative methodological choices. These include the construction of region-specific poverty linesand the empirical model of poverty determinants used. Estimates of poverty levels and the results of the model are presented, followed by simulations that indicate the impact on poverty of specific policy interventions." -- from Text